2014
DOI: 10.1021/la503468z
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Hybrid (Electrostatic Double-Layer and Faradaic Capacitor-Based) Polymer Actuators Incorporating Nickel Oxide and Vapor-Grown Carbon Nanofibers

Abstract: The electrochemical and electromechanical properties of polymeric actuators prepared using nickel peroxide hydrate (NiO2·xH2O) or nickel peroxide anhydride (NiO2)/vapor-grown carbon nanofibers (VGCF)/ionic liquid (IL) electrodes were compared with actuators prepared using solely VGCFs or single-walled carbon nanotubes (SWCNTs) and an IL. The electrode in these actuator systems is equivalent to an electrochemical capacitor (EC) exhibiting both electrostatic double-layer capacitor (EDLC)- and faradaic capacitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…In order to promote the actuation performance, electrochemically active materials such as metal oxides, conducting polymers, and heteroatoms doping were introduced, which could improve the electrochemical activity of carbon materials and thus enhance device performance in many applications, including capacitors, lithium ion batteries, and electrocatalysts . In the field of electrochemical actuators, Asaka's group reported the method of adding metal oxide nanoparticle (RuO 2 and NiO 2 ) into nanocarbon materials, and the actuation deformation was enhanced by the faradic capacitance that captured extra electron for more cation accommodation. Wallace et al reported polypyrrole and polypyrrole/CNT based electrochemical actuator where polypyrrole generated large redox process to uptake more ion in electrode, resulting in an increase of actuation strain levels.…”
mentioning
confidence: 99%
“…In order to promote the actuation performance, electrochemically active materials such as metal oxides, conducting polymers, and heteroatoms doping were introduced, which could improve the electrochemical activity of carbon materials and thus enhance device performance in many applications, including capacitors, lithium ion batteries, and electrocatalysts . In the field of electrochemical actuators, Asaka's group reported the method of adding metal oxide nanoparticle (RuO 2 and NiO 2 ) into nanocarbon materials, and the actuation deformation was enhanced by the faradic capacitance that captured extra electron for more cation accommodation. Wallace et al reported polypyrrole and polypyrrole/CNT based electrochemical actuator where polypyrrole generated large redox process to uptake more ion in electrode, resulting in an increase of actuation strain levels.…”
mentioning
confidence: 99%
“…Terasawa et al [49] presented the incorporation of metal oxide particles such as RuO 2 , NiO 2 , MnO 2 , or IrO 2 [50] with carbon materials. 1 wt% of RuO 2 into multi-walled carbon nanotubes (MWCNTs) electrode can increase the C sp from 30 to 80 F/g.…”
Section: Nanocomposites With Ruomentioning
confidence: 99%
“…In electric double layer charging and discharging process, there is no electrochemical reaction and there is only accumulation of charge at the electrode/electrolyte interface whereas in faradic reaction the charge takes part in the oxidation or reduction reactions of the polymer [41]. There are attempts to improve the actuation by using both processes by combining electrochemically active PEDOT:PSS and inactive components such as carbonbased materials together in electrode preparation [41,42]. Physically it is rather complicated to measure or separate the charge contributed by each of the processes but through simulation, we separate and provide the charge contribution by each process providing new insights in the underlying kinetics in the PEDOT:PSS printed actuators fabricated in this work.…”
Section: Introductionmentioning
confidence: 99%